Rentabilidad de la Distribuidora Touma S.A Ditosa de la ciudad de Babahoyo, provincia de Los Ríos, durante el periodo 2021- 2023. - López Robayo, Miguel Ángel (2024)
In this research, DITOSA, a company based in the city of Babahoyo, province of Los Ríos, specialized in the retail sale of construction materials, was studied. This study was carried out with the objective of determining the trend of the company's financial profitability. To achieve this objective, a documented investigation was carried out, using reliable sources that helped us in the development of this study. We also visited the company's facilities to communicate with the general manager, to whom we conducted an interview that was crucial in identifying the problem that DITOSA was going through. We also used quantitative methodology, where comparative financial analyses referring to the period 2021-2023 were applied. Among them, vertical and horizontal analyses were applied to measure the trends of the items and the use of financial ratios, which allowed us to reach solid and well-founded conclusions. In conclusion, it was determined that the low profitability in the company was the result of the low inventory capacity and therefore presents a low liquidity to meet its long-term obligations, and given these results, recommendations were provided to improve the financial health of DITOSA.